The Relationship Between Family Support and Clean and Healthy Living Behavior in the Household Order - Dela Saputri; Suratini; Yuli Isnaeni (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background:Clean and healthy living behavior (PHBS) is used as a parameter for achieving increased health coverage in the 2015 - 2030 Sustainable Development Goals (SDGs) program, but until now it is still the center of government attention. If PHBS is not implemented properly, several diseases will emerge, including diarrhea, ARI, TB and malaria. For the implementation of PHBS to be good, there must be family support. Objective:To determine the relationship between family support and clean and healthy living behavior in the household structure of productive age in Kajar 2 Hamlet, Karangtengah, Wonosari, Gunungkidul. Method:This research is correlational research with a cross sectional approach. The sampling technique uses a simple random sampling method. The sample in this study was early adulthood (18 – 40 years) as many as 67 people who lived in Kajar 2 Hamlet, Karangtengah, Wonosari, Gunungkidul. The data analysis technique uses the Kendall Tau test. Results:The results of the Kendall Tau test show that there is a relationship between family support and clean and healthy living behavior, household order in productive age in Kajar 2 Hamlet, Karangtengah, Wonosari, Gunungkidul with a p value = 0.000 (p<0.05) and a closeness value of 0.724. indicates a strong relationship. Conclusion:There is a relationship between family support and clean and healthy living behavior in the household structure at productive age in Kajar 2 Hamlet, Karangtengah, Wonosari, Gunungkidul.